PENGARUH EDUKASI MENGGUNAKAN MEDIA AUDIO VISUAL (INSTAGRAM) TERHADAP PENGETAHUAN GIZI PADA SISWI ANEMIA - Suni, Syahrizal Rahman; Priyatama, Aditya Nanda; Sari, Yulia (Media Penelitian dan Pengembangan Kesehatan, 2024)
Adolescence is a transition period from childhood to adulthood that is vulnerable to nutritional problems, especially anemia. Lack of nutritional knowledge is one of the causes of this situation. Education is an effort that can be made to increase knowledge and prevent anemia in adolescents. This study aimed to analyze the effectiveness of nutrition education Instagram on nutritional knowledge in anemic schoolgirls. The research was conducted at SMK N 1 Banyumas in December 2023-February 2024. The method used a Quasi-experiment with a pre-post-test with a control group design. The study was conducted with a total of 32 anemic schoolgirls obtained using purposive sampling who were divided into 2 groups. The intervention group used audio-visual as nutrition education, while the control group received counseling in the end of this study. Knowledge data was obtained using a questionnaire and data analysis using the independent t-test. The study result showed there was an effect of nutrition education using audio-visual media on increasing knowledge in anemic female student (p = 0.000). Nutrition education using Instagram audio-visual media was significant in increasing nutritional knowledge in anemic female students.